Kegagalan kerjasama politik UMNO dan PAS dari 2018 hingga 2022 - Roslee, Mehat (2023)
BN’s defeat in GE 14 had propelled the party to decide on its new direction. One important new direction of UMNO was to establish a cooperation with PAS. This study would identify relationship pattern between UMNO and PAS pre GE 14, investigate factors resulting in the need for UMNO and PAS cooperation to be established in the aftermath of GE 14 and investigate factors causing UMNO and PAS cooperation to crumble pre GE 15. This study was held using qualitative method through content analysis on reports of newspapers, speeches, interviews and newsportals. This study found that UMNO and PAS cooperation was easily established in the aftermath of GE 14 due to the closeness in the relationship between the two parties pre GE 14. UMNO and PAS cooperation in the aftermath of GE 14 was built on a very strong foundation, which is the realization that it will bring victory, sharing of a similar ideology between UMNO and PAS and the failure of PH Government to take care of the Malay Muslim interests. However, out of control factor arose causing in the fracture of UMNO and PAS cooperation in the aftermath of GE 14, which is the fall of PH Government from power that made the raison detre for cooperation between the two parties disappear. The cooperation then crumbled due to the “two faced” stand of PAS which was resulted by the appearance of BERSATU as an intruder to this cooperation. UMNO’s confidence on its good performance in the state elections of Melaka and Johor meanwhile made UMNO determined to sever its tie with BERSATU, while PAS was still loyal to BERSATU, hence bringing this cooperation to crumble.